Adverse drug reactions of antihypertensive agents at tertiary care hospital in central Nepal - Paudel, Sabita; Chetty, M Sudarsana; Laudari, Shankar; Subedi, Nuwadatta (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Acute Hypertension is the most common condition seen in primary care and leads to myocardial infarction, stroke, renal failure, and death if not detected early and treated appropriately. The study was conducted with the objective to examine the incidence of different types of adverse drug reactions in drug treated hypertensive patients. Materials & Methods: Patients (n=382) who received antihypertensive agents were selected and interviewed using a standardized questionnaire. The Naranjo Algorithm, which categorizes the causality relationship into definite, probable, possible and doubtful, was used for the assessment of the exact nature of Adverse drug reaction (ADR). Results: Calcium channel blockers (CCBs) were the drug class with highest number (22 or 32.84%) of ADRs followed by Angiotensin-converting enzyme Inhibitors (ACEI) in 17 (25.38%), Angiotensin Receptor Blockers (ARB) in 12 (17.91%), diuretics in 10 (14.92%) and beta adrenergic antagonist in six (8.95%). Cardiovascular system (40 or 59.70%) was the most affected followed by central nervous system (16 or 23.88%) and respiratory and dermatological system each in 11 (16.42%) cases. On Naranjo’s probability scale, nine (13.4%) of the ADRs were definite, 39 (58.2%) possible, 16 (23.9%) probable and three (4.5%) doubtful. Conclusion: Calcium channel blockers were mostly associated with ADRs while Cardiovascular system was the most frequently affected.